2015
DOI: 10.1097/icl.0000000000000141
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Involvement in Systemic Inflammatory Diseases

Abstract: Corneal involvement in patients with systemic inflammatory disorders may be sight threatening, and it may be associated with a life-threatening disease. Significant systemic inflammatory diseases in this context are autoimmune connective tissue diseases, systemic autoimmune dermatological disorders, and autoimmune diseases of the lacrimal system. Keratoconjunctivitis sicca is usually the most common ocular finding in these patients. Peripheral ulcerative keratitis is a rare condition usually associated with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 47 publications
0
12
0
2
Order By: Relevance
“…Corneal stroma, which comprised 90% of total corneal thickness, was the major part that contributed to the corneal biomechanical properties [16]. Various conditions associated with corneal stromal inflammation such as keratoconus, Sjogren syndrome, herpes stromal keratitis have shown to be associated with more compliant corneas [32][33][34][35][36]. Despite that the immunopathogenesis of DED has not yet been fully understood, numerous studies have concluded that ocular surface inflammation displayed a critical role [37][38][39].…”
Section: Plos Onementioning
confidence: 99%
“…Corneal stroma, which comprised 90% of total corneal thickness, was the major part that contributed to the corneal biomechanical properties [16]. Various conditions associated with corneal stromal inflammation such as keratoconus, Sjogren syndrome, herpes stromal keratitis have shown to be associated with more compliant corneas [32][33][34][35][36]. Despite that the immunopathogenesis of DED has not yet been fully understood, numerous studies have concluded that ocular surface inflammation displayed a critical role [37][38][39].…”
Section: Plos Onementioning
confidence: 99%
“…The problems that remain to be solved are questions for antigen recognition mechanisms involved in triggering the systemic inflammatory conditions induced by pollen exposure in patients with immune-mediated SIDs. A previous study reported that corneal involvement in patients with systemic inflammatory disorders may be sight-threatening and associated with a life-threatening disease [17].…”
Section: The Limits Of Our Study and Other Issuesmentioning
confidence: 99%
“…Conjunctivitis, episcleritis, scleritis, and anterior uveitis are by far the most prevalent EIMs surveyed in the literature, while corneal changes are unfairly underrepresented among them although the cornea is a notably predisposed site to immune-related disorders due to its large content of collagen. 5 To the best of our knowledge, no investigation of corneal and other anterior segment parameters has been reported in patients with IBD thus far. For this reason, the primary aim of our study was to evaluate various anterior segment parameters in IBD patients, while the secondary aim was to appraise associations between anterior segment values and other clinical variables with special interest in dry eye disease (DED).…”
Section: Introductionmentioning
confidence: 99%